To evaluate the left-hand side of the equation given:
\[ \frac{x^{\frac{5}{3}}}{x^{\frac{3}{2}}} \]
we use the property of exponents that states:
\[ \frac{x^m}{x^n} = x^{m-n} \]
In this case, let \( m = \frac{5}{3} \) and \( n = \frac{3}{2} \). We first need to find \( m - n \):
- Convert both fractions to have a common denominator. The least common multiple (LCM) of 3 and 2 is 6.
-
For \( \frac{5}{3} \), convert it: \[ \frac{5}{3} = \frac{5 \times 2}{3 \times 2} = \frac{10}{6} \]
-
For \( \frac{3}{2} \), convert it: \[ \frac{3}{2} = \frac{3 \times 3}{2 \times 3} = \frac{9}{6} \]
- Now subtract the two fractions: \[ \frac{10}{6} - \frac{9}{6} = \frac{10 - 9}{6} = \frac{1}{6} \]
Thus, we have: \[ \frac{x^{\frac{5}{3}}}{x^{\frac{3}{2}}} = x^{\frac{1}{6}} \]
So now we can write our original equation as: \[ x^{\frac{1}{6}} = x^a \]
Since the bases are the same, we equate the exponents: \[ \frac{1}{6} = a \]
Therefore, the value of \( a \) is: \[ \boxed{\frac{1}{6}} \]